Above-ground biomass estimation for a shrubby mistletoe in an Amazonian savanna. (11th November 2019) - Fadini, Sarah Rosane M. C.; Barbosa, Reinaldo I.; Rode, Rafael; Corrêa, Viviane; Fadini, Rodrigo F.
Abstract: Mistletoes are considered keystone species on woodlands and savannas worldwide, providing a food resource for a diversified fauna, as well as a nutrient-enriched litter. Infections can be large (∼1–3 m) and, in some parts of the Amazonian savannas, parasitize up to 70% of hosts locally. Despite these facts, biomass of mistletoes is rarely investigated. Here we constructed allometric models to predict the biomass stock of the shrubby mistletoe Psittacanthus plagiophyllus in an Amazonian savanna. In addition, we determined whether host size could be used as a proxy for mistletoe biomass. Finally, we compared the biomass of mistletoes with that of trees, to evaluate their relative importance. We have shown that: (1) biomass of leaves (46.1% ± 13.5%) are as important as of stems (47.8% ± 13.5%), and relative contribution of stems increases as plant grows; (2) the model including width, breadth and vertical depth was the best (SE = 0.39, R 2 = 0.9) for predicting individual mistletoe biomass; (3) mistletoe load and biomass per host had a positive, but weak (R 2 = 0.11 and 0.09, respectively), relationship with host size, and thus such host information is a poor predictor of mistletoe biomass; and (4) in comparison with trees, mistletoes constituted less than 0.15% (0.5–22 kg ha −1 ) of the total above-ground biomass, suggesting that this life-form is irrelevant to the local biomass stock despite its unequivocal biological importance.